Tensor fascia lata free flap as salvage solution minimizes donor site morbidity in anterolateral thigh free flap failure—decision making algorithm and a case report - Soemmer, Christian; Bicsák, Ákos; Vitkos, Evangelos N.; Brockmeyer, Phillipp; Haßfeld, Stefan; Bonitz, Lars (Frontiers in Surgery, 2025)
BackgroundThe anterolateral thigh (ALT) free flap is a workhorse in head and neck reconstruction, offering versatility, long pedicle length, and low donor site morbidity. Nevertheless, anatomical variability of its perforators can occasionally result in absent or unusable vessels, jeopardizing intraoperative feasibility. In such cases, harvesting an additional donor site increases operative time, morbidity, and aesthetic results. Salvage solutions within the same vascular territory are therefore essential to ensure safe and efficient reconstruction.Case presentationWe report a 70-year-old female with oral squamous cell carcinoma of the right retromolar triangle requiring composite resection with flap reconstruction. A patient-specific reconstructive plate and ALT free flap were planned. Intraoperatively, no usable perforators of the descending branch of the lateral circumflex femoral artery were identified. Proximal dissection revealed reliable perforators supplying the tensor fascia lata (TFL) territory, allowing elevation of a TFL free flap through the same incision. Microvascular anastomosis was performed successfully. The postoperative course was uneventful, and the flap remained viable throughout follow-up.ConclusionThis case highlights the importance of intraoperative flexibility when encountering ALT perforator absence. The TFL free flap represents a dependable salvage solution, characterized by more consistent vascular anatomy and minimal additional donor site morbidity. By enabling conversion within the same surgical field, the TFL flap reduces operative time and avoids the drawbacks of a second donor site. Incorporating this strategy into a structured decision-making algorithm enhances reconstructive safety and broadens the armamentarium for complex head and neck reconstruction.